Analysis of Human Resources Performance in the Field of Umrah Travel Administration (Zafa Tour) PT. Zafa Mulia Mandiri Bengkulu - Khairul Anwar; Idwal B; Faisal Muttaqin; Zelvia Liska Afriani (Sharia Economic and Management Business Journal (SEMBJ), 2023)
Administration in a company holds considerable control, coordinating all the interests and objectives of the organization or company that is carried out so that it can be united and can be in line with the same place and time, employee assessments must be compared with the targets and standards that have been set. Competition in the business world or business, you could say that competing in the business world is one of the main things that cannot be avoided, so it should be faced and lived. Competition starts from the world of small businesses and the world of large or broad businesses. One of them, for example, such as competition in the Hajj and Umrah travel agency The research method used is a qualitative research method with data collection techniques using observation interviews and documentation as well as informants in this study, namely the filing and equipment section, the data obtained is processed then analyzed comparisons and conclusions This study shows that the performance of the Umrah travel administration is quite tense because it is not only taking care of finances, it turns out that sometimes you have to take care of banners and also browsers for partners, sometimes you also have to take the passports of pilgrims registered by partners.